Antenatal screening and diagnosis of tuberous sclerosis complex by fetal echocardiography and targeted genomic sequencing. Issue 15 (April 2018) - Gu, Xiaoyan; Han, Ling; Chen, Jian; Wang, Jianbin; Hao, Xiaoyan; Zhang, Ye; Zhang, Jun; Ge, Shuping; He, Yihua
Abstract : Abstract: Although fetal cardiac rhabdomyoma can be the initial finding in patients with tuberous sclerosis complex (TSC), the challenges of precise genetic diagnosis of TSC can now be potentially overcome by new whole or targeted genomic sequencing. The goals of this study were to investigate the correlation between suspected cardiac rhabdomyoma and TSC to provide the information for a prenatal diagnosis of TSC and to validate the TSC genotype in this cohort of fetuses with suspected prenatal cardiac rhabdomyoma. We retrospectively analyzed 10, 728 fetal echocardiograms from January 2013 to March 2016 in our institution. A total of 32 fetuses were suspected of having cardiac rhabdomyomas. Among them, 15 subjects met the inclusion criteria and provided written consent. Samples from fetuses (n = 13 after terminations) and newborns (n = 2) were available for targeted genomic sequencing of the exons and introns of the TSC1 and TSC2 genes and the adjacent 10 base pairs and for validated studies using Sanger sequencing. Among the 15 subjects with suspected cardiac rhabdomyoma and TSC genomic sequencing data, 7 subjects were familial and 8 subjects were sporadic cases. Fetal echocardiography showed a single tumor in 2 fetuses and multiple tumors in 13 fetuses. Gene sequencing analysis showed no mutation of the TSC1 or TSC2 gene in 2 subjects with a single tumor but positive mutations in all 13 subjects with multiple tumors. Among the latter, 5 mutations were "pathogenic" and have been previously reported (4 familial and 1 sporadic). Six new mutations were "likely pathogenic" and had not been previously reported (3 familial and 3 sporadic); 1 was of "uncertain significance" (sporadic), and 1 was suspected of being "likely benign" (sporadic). Prenatal suspected cardiac rhabdomyoma detected by fetal echocardiography should raise the suspicion of TSC. In fetuses with multiple tumors, especially the familial cases, genomic sequencing has a high yield of detecting TSC-causing genes. Patient history, prenatal fetal echocardiography, and targeted genomic sequencing may facilitate screening for, diagnosis of, and counseling for TSC.